Reducing maltreatment recurrence through home visitation: A promising intervention for child welfare involved families - Lee, Eunju; Kirkland, Kristen; Miranda-Julian, Claudia; Greene, Rose (Child abuse & neglect, 2018)
Maltreatment of children is a key predictor of a range of problematic health and developmental outcomes. Not only are affected children at high risk for recurrence of maltreatment, but effective interventions with known long term impact are few and limited. While home visiting is one of the most tested secondary prevention models for improving parenting, its primary focus on young primiparous mothers underemphasizes one of the most important risk groups: child welfare involved multiparous mothers. This study's focus is a randomized controlled trial of Healthy Families New York that included a subgroup of mothers (n = 104) who had at least one substantiated child protective services (CPS) report before enrolling in the program. By the child’s seventh birthday, mothers in the home visited group were as half as likely as mothers in the control group to be confirmed subjects for physical abuse or neglect (AOR = .46, p = .08). The number of substantiated reports for mothers in the control group was twice as high as for those in the home visited group (1.59 vs. 79 p = .02, ES = .44). Group differences were only observed after the child's third birthday, suggesting the possible effect of surveillance in early years. Post-hoc analyses indicate that home visited mothers had fewer subsequent births that may have contributed to less parenting stress and improved life course development for mothers. In light of our findings, we suggest considering and further testing home visiting programs as a tertiary prevention strategy for child welfare-involved mothers.